Postoperative ecchymoma of eyelid after botulinum toxin injection for hemifacial spasm: a case report - Hu, Xinyu; Guo, Kexin; Li, Jingwen; Wang, Xinyi; Liu, Hanshu; Yu, Qinwei; Kuang, Guiying; Li, Gang; Huang, Jinsha; Li, Hongge; Lin, Zhicheng; Xiong, Nian (Frontiers in Neurology, 2023)
Hemifacial spasm (HFS) is a rare movement disorder characterized by involuntary muscle contractions on one side of the face. Compared to the high therapeutic effect, adverse effects of botulinum toxin treatment for HFS occurred rarely. However, managing HFS patients who are also taking antithrombotic drugs poses a challenge. Here, we present a case of postoperative ecchymoma of the eyelid following a botulinum toxin injection in a patient receiving daily vinpocetine and aspirin antiplatelet therapy. This case highlights the importance of considering the potential risks and formulating a treatment plan that maximizes benefit while minimizing complications in HFS patients undergoing botulinum toxin injections and taking antithrombotic medications. To the best of our knowledge, this is the first reported case of postoperative ecchymoma of the eyelid following a botulinum toxin injection. Further research and additional case reports are needed to better understand the management strategies for this patient population.